Surefire Strategy: Budget Literacy and Participation as Key to Improving University Performance - Susilowati, Nuri; Sari, Tri Diana; Wahyudi, Teguh; Hayati, Masita Nur (Technium Social Sciences Journal, 2025)
Budget literacy and budget participation are important factors in effective financial management in universities. However, research on their influence on university performance is still limited, especially at Surabaya State University, where suboptimal budget management is still a major challenge. This study aims to examine the contribution of budget literacy and participation in budget management to improving university performance, as well as the relationship between good budget understanding and the involvement of various parties in the budgeting process. A combined survey and Focus Group Discussion (FGD) research method was conducted with 20 informants. The results showed that good budget literacy promotes transparency and accountability in fund management, while participation in the budgeting process increases the efficiency and accuracy of fund allocation. Budget literacy and budget participation can improve university performance. Their improvement supports more efficient, transparent, and accountable financial management, which in turn improves the quality of education, facilities, and community service at the university.